The Influence of Psychological Safety, Collectivism, and Power Distance on Innovation Performance Mediated by Organizational Commitment And Performance Management Context Among Employees of XYZ School - Meis Sh. Louhenapessy; Oliandes Sondakh (Journal of World Science, 2026)
This study examines the effects of psychological safety, collectivism, and power distance on innovation performance, with organizational commitment and performance management context posited as mediators, at XYZ School. The sample comprised 47 employees (teachers and staff). Data were collected via questionnaires and tested using path analysis. The results indicate that collectivism has a positive and significant effect on organizational commitment (? = 0.665; t = 4.629; p = 0.000), thus supporting H2. Collectivism also significantly and positively affects performance management context (? = 0.533; t = 2.937; p = 0.003), supporting H5. Regarding the final outcomes, organizational commitment does not significantly influence innovation performance (? = 0.051; t = 0.244; p = 0.807) — H7 rejected — whereas performance management context has a significant positive effect on innovation performance (? = 0.473; t = 2.113; p = 0.035) H8 accepted. In sum, a collectivist organizational culture strengthens organizational commitment and fosters a supportive performance management context, and it is the latter (performance management context) that significantly drives innovation performance. Psychological safety and power distance did not show direct significant impacts in this sample. The findings imply that school management should prioritize strengthening collective values and improving performance management practices to stimulate innovation